The quality of the organic materials determines its carbon conversion efficiency in tropical latosol - Song, Shuhui; Liu, Siru; Liu, Yanan; Shi, Lei; Li, Huayong; Shi, Weiqi; Ma, Haiyang (Frontiers in Microbiology, 2025)
IntroductionTropical regions are characterized by high temperatures and abundant rainfall, which facilitate rapid carbon mineralization. However, research on soil organic carbon conversion efficiency (Esoc) in these areas is currently constrained by a lack of robust data support.MethodsThis study used nylon - bags with typical tropical organic materials (pineapple leaf (PAL), banana stems (BAS), coconut husk (CCH), and organic fertilizer (OF)) to explore how mixing straw with latosol impacts soil organic carbon conversion efficiency (Esoc) and products, and to understand the relationships among Esoc, material composition (glycolipid, hemicellulose, cellulose, lignin), and enzyme activity.ResultsCCH had the highest Esoc, from 37.79% to 96.87%, followed by OF with 26.71%–63.12%. The Esoc of PAL and BAS was 34.57% and 25.32% at 90 days, and 7.59% and 2.55% at 1080 days. The main factor that determines the difference in carbon conversion efficiency is the composition of organic materials. Compared with CK treatment, the soil organic carbon for PAL and BAS at 90_days was mainly O–alkyl–C, anomertic–C, and N–alkyl/methoxyl–C, with an unstable structure. The decomposition products of CCH mainly consisted of anomertic–C, aromatic–C, O–alkyl–C, carbonyl–C, and N–alkyl/methoxyl–C. The increased organic carbon in OF - mixed soil was mainly N–alkyl/methoxyl–C and anomertic–C. In the short-term (90 days), PAL, BAS, and OF increased the quantity and diversity of soil microorganisms, as well as the activities of xylosidase and cellobiohydrolase. CCH mainly enhanced soil phenol oxidase activity and maintained microbial biomass stabilityin the long-term (1080 days).DiscussionThis study revealed the changes of microbial diversity and enzyme activity under different organic materials. The promotion effects of PAL and BAS on microbial biomass, diversity and enzyme activity in the short term and the maintenance effects of CCH on the stability of microbial biomass in the later period were investigated, which provided a new basis for further exploring the function and mechanism of microorganisms in soil ecosystems.